Gestão estratégica e as competências gerenciais na estrutura administrativa das organizações - Bolzan, Alexandre Galina (2007)
This work presents an analysis of the managerial competences of the Administrative Managers of 2 located companies in the municipal district of Santa Maria, State of Rio Grande do Sul. The general objective of the research is to identify the managerial competences of the Administrative Managers through an acting evaluation or evaluation of 360 degrees. To reach this I aim at, they were established the following specific objectives: (1) to identify which are the main models of strategic administration proposed at the present time by the authors for the organizations; (2) to evaluate which are the different structures found in the companies that will be researched and the Administrative Manager's different functions; (3) for the studied companies, to identify which are the expected managerial competences and presents regarding the Administrative Manager. Owed the proximity and to the access, we opted for a sampling for convenience, being chosen 2 companies of different sections (mechanical metal and production of soft drinks) and that they present strategic planning in their activities. In these two companies, a questionnaire can be applied where identified the administrative manager's managerial competences and the different forms that the Administrative Management is structured. With the identification of the competences you manage and the different found administrative structures, it can finally to do a relationship of the profile of this professional's competences.